Media technology is not the culprit: Factors influencing users’ quarrelsome behavior in political social platform use - Zhong Fangqi; Lian Shuixing; Song Meijie; Yan Lingyan (PLoS ONE, 2025)
Social platforms are seen as hotbeds of political debate, where squabbles between users with different views and positions have become commonplace. From the perspective of social cognition, this study considered the individual variables (degree of political firmness and political efficacy) and situation variables (news credibility and life satisfaction) synthetically to construct a structural equation model. The purpose of this study was to explore the factors influencing users’ quarrelsome behavior in political use on social platforms. The results show that users’ political firmness, the credibility of news in the media environment, and real-life satisfaction all contribute to their quarrelsome behavior on social platforms.